2005
DOI: 10.1007/bf03395527
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings on the Effects of Self-Referring and Evaluative Stimuli on Stimulus Equivalence Class Formation

Abstract: Thirty-two subjects completed 2 stimulus equivalence tasks using a matching-to-sample paradigm. One task involved direct reinforcement of conditional discriminations designed to produce derived relations between self-referring stimuli (e.g. , me, myself, I) and positive evaluation words (e.g., whole, desirable, perfect). The other task was designed to produce derived relations between selfreferring stimuli and negative evaluation wordls (e.g., unworthy, flawed, inadequate). Performance on each task was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
1
18
0
3
Order By: Relevance
“…It shows that state self-esteem can be influenced by how a person integrates performance feedback (negative or positive). Previous studies mainly focused on the interaction between environmental feedback and individuals' self-concept (e.g., Healy, Barnes-Holmes, Barnes-Holmes, & Keogh, 2008;Merwin & Wilson, 2005), but few studies have paid attention to the effect of inner feedback of individuals' own behaviors on their self-concept. This study showed that individuals could actively adopt some strategies to influence their own self-concept.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…It shows that state self-esteem can be influenced by how a person integrates performance feedback (negative or positive). Previous studies mainly focused on the interaction between environmental feedback and individuals' self-concept (e.g., Healy, Barnes-Holmes, Barnes-Holmes, & Keogh, 2008;Merwin & Wilson, 2005), but few studies have paid attention to the effect of inner feedback of individuals' own behaviors on their self-concept. This study showed that individuals could actively adopt some strategies to influence their own self-concept.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Social threat words were compiled from word lists used in previous studies of socially threatening stimuli (Wenzel, Jackson, & Holt, 2002;Heinrichs, Hofmann, & Barlow, 2004;Merwin & Wilson, 2005;Munafo, Hayward, & Harmer, 2006). Neutral words were chosen from the Affective Norms for English Words (ANEW) database, a list of over 1,000 words with ratings of pleasure, arousal, and dominance on scales from 1-9 (Bradley & Lang, 1999).…”
Section: Priming Words-mentioning
confidence: 99%
“…This finding was not attributable to an inability by participants with mild mental disabilities to form equivalence relations, as all participants were required to pass a preliminary task in which arbitrary stimuli were used in order to be included in the analysis. Merwin and Wilson (2005) demonstrated a similar disruption of equivalence learning as a function of self-evaluative thoughts and feelings. Specifically, individuals who endorsed low self-esteem had more difficulty deriving a relationship between self-referential words (i.e., me, myself, and I) and positive evaluative words (i.e., worthy, complete, and competent) than the high-esteem participants.…”
mentioning
confidence: 80%